Gênero alegre, pornografia e representações femininas: um estudo sobre o jornal O Rio Nu (1898-1916) - Costa, Johnatas dos Santos (2021)
Known for its simple and cunning language, its illustrations of half-naked women and a humorous and malicious text, the newspaper of “gênero alegre” O Rio Nu circulated in the city of Rio de Janeiro and beyond between 1898 and 1916. This work aims to understand two facets of this successful journal: its posture as a moral transgressor and as a civilizing “educator”. At first, we will understand how a controversy, in 1910, involving the printed and the director of the Post Office, Joaquim Ignácio Tosta, reveals to us about the views that some sectors of Rio de Janeiro society, in the early 1900s, had about obscenity and pornography. In the second part of the research, we will present the journal as a perpetuator of social conceptions about women. Through the study of short stories published by the printed, we will understand which representations of women were disseminated in order to highlight a civilizing attitude of O Rio Nu towards its male readers by forging a model of femininity that should be desired by them.